2014
DOI: 10.1002/14651858.cd007364.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Heparin versus normal saline for patency of arterial lines

Abstract: The available evidence is of poor quality because of risk of bias and does not provide sufficient information to support the effects of adding heparin (1 to 2 IU/mL) to a maintenance solution (pressurized to deliver 3 mL of flush solution per hour) of 0.9% normal saline in maintaining the patency and functionality of arterial catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Heterogeneity was assessed using the Cochran Q and I 2 statistics. For the Q statistic, a P value<0.10 was considered statistically significant for heterogeneity; for the I 2 statistic, heterogeneity was interpreted as absent (I 2 : 0–25%), low (I 2 : 25.1–50%), moderate (I 2 : 50.1–75%), or high (I 2 : 75.1–100%) [ 18 ]. Subgroup analyses were carried out according to: (i) study quality, (ii) study design (cohort versus case-control studies), (iii) geographic location (Europe vs. Asia vs. North America), and (iv) number of adjustment factors (n ≥5 vs. n ≤6).…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity was assessed using the Cochran Q and I 2 statistics. For the Q statistic, a P value<0.10 was considered statistically significant for heterogeneity; for the I 2 statistic, heterogeneity was interpreted as absent (I 2 : 0–25%), low (I 2 : 25.1–50%), moderate (I 2 : 50.1–75%), or high (I 2 : 75.1–100%) [ 18 ]. Subgroup analyses were carried out according to: (i) study quality, (ii) study design (cohort versus case-control studies), (iii) geographic location (Europe vs. Asia vs. North America), and (iv) number of adjustment factors (n ≥5 vs. n ≤6).…”
Section: Methodsmentioning
confidence: 99%
“…Heparinized saline solution is known as a common solution in maintaining catheter patency and effectiveness ( 13 ). However, adverse effects of heparinized saline solution and effect of normal saline in maintaining patency of arterial catheter lead to controversy over the type of flush solutions to maintain catheter effectiveness ( 10 , 15 - 17 ). In a recent systematic review, Kordzadeh et al ( 15 ) concluded that heparinized saline solution may be better for long-term use of arterial line.…”
Section: Discussionmentioning
confidence: 99%
“…Normal arterial waveform contains the following components: Ascending slope of systolic arterial pressure, peak systolic arterial pressure, descending slope of systolic arterial pressure, dicrotic notch, continue of blood flow through the artery to the vein based on the pressure gradient and end-diastolic pressure ( 5 ). Heparinized saline solution is widely used to prevent occlusion of arterial catheters in intensive care units ( 10 ). Heparin has effects at multiple sites of the intrinsic and extrinsic coagulation pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Normal or isotonic saline has sodium and chloride concentrations of 154 mEq/L. 8 Normal saline solution can maintain patency of arterial and central venous pressure monitoring catheters. Heparinized solutions had no effect on prolonging patency and improving function of catheters and even caused changes in activated partial thromboplastin time (APTT) while the normal saline solution increases accuracy of coagulatory tests.…”
mentioning
confidence: 99%